Pelayanan Berbasis Digital: Implementasi Aplikasi Pendaftaran Antrian Paspor Online (APAPO) di Kantor Imigrasi Tanjungpinang - Putri Febriyanti; Herlina Amelia Putri; Cindea Putri Ananda Iskandar (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This The development of this information technology is utilized by the Immigration Class 1 TPI Tanjungpinang to improve services by making it easier for people to register for passport applications with the support of the Online Passport Queue Registration Application (APAPO) which has been used since January 2019. The application of this Online Passport Service is a form of service improvement carried out by the Tanjungpinang City Immigration Office to handle public complaints regarding the queue for passport processing. Online passport services can be downloaded via smartphones in the Playstore and Appstore. At the Immigration Office Class 1 TPI Tanjungpinang there is information on a stop extortion poster, but the reality is that extortion is still being carried out by civil servants at the passport application service. This research was conducted using qualitative research methods. This method is used in the process of data acquisition and data analysis process. The qualitative method used tends to be descriptive in terms of obtaining and analyzing money data. Implementation is a plan that has been conceptualized in carrying out a clear goal. Implementation itself certainly has a goal, the purpose of an implementation is to realize a plan that has been structured that can be implemented properly. The online passport queue application is a new output issued by the government in carrying out digital-based innovations that can be carried out by the community and make it easier for the community.